Multigroup Ethnic Identity Measure: factorial structrure in Ukrainian immigrants in western Europe - Frias-Navarro, Dolores; Botvyn, Yanina; Pascual-Soler, Marcos; Berrios-Riquelme., Jose (Opción)
The objective of this study is to evaluate the factorial structure of the Multigroup Ethnic Identity Measure on Ukrainians immigrants in two countries of Occidental Europe. The factorial structure was put to test with a confirmatory factorial analysis and with the factorial invariance between the samples of both countries. The results indicate that the twodimensional structure has a better adjustment than the one-dimensional, two dimensions have a good internal consistency and they are directly correlated. The factorial invariance between both countries has also been proved. It is concluded that the measure presents a twodimension structure and suggestions for future investigations are proposed.